2003
DOI: 10.1167/iovs.02-1147
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Liver Metastasis of Intraocular Melanoma by Interferon-β Gene Transfer

Abstract: The results support the feasibility of activation of NK cell function through gene transfer as one possible therapeutic strategy for reducing hepatic metastases of uveal melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
1
29
0
2
Order By: Relevance
“…The liver enzyme aspartate transaminase (AST) was significantly lower (P < 0.05, Mann-Whitney U test) in melittin-loaded nanoparticle-treated mice (329 ± 162 U/l) than in saline-treated controls bearing tumors (2097 ± 1162 U/l). Because elevated levels of AST commonly accompany liver metastases, the lower levels in the treated mice are consistent with inhibition of liver metastases (32,33), although this remains to be proved.…”
Section: Melittin-loaded Nanoparticle Synthesis and Action On Cancer mentioning
confidence: 96%
“…The liver enzyme aspartate transaminase (AST) was significantly lower (P < 0.05, Mann-Whitney U test) in melittin-loaded nanoparticle-treated mice (329 ± 162 U/l) than in saline-treated controls bearing tumors (2097 ± 1162 U/l). Because elevated levels of AST commonly accompany liver metastases, the lower levels in the treated mice are consistent with inhibition of liver metastases (32,33), although this remains to be proved.…”
Section: Melittin-loaded Nanoparticle Synthesis and Action On Cancer mentioning
confidence: 96%
“…9 This hypothesis is supported by numerous studies using gene therapy approaches in both murine and human solid tumor models. [10][11][12][13][14][15][16][17] Moreover, we and others have shown that intralesional delivery of the IFN-b gene, which allows for the accumulation of higher intratumoral concentrations of IFN-b, is able to suppress primary tumors, prolong the survival of tumor-bearing mice, and protect against a second challenge in syngeneic mice. 12,18,19 Nitric oxide (NO) is a small molecule produced by mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43][44][45][46][47] The mechanism of action is complex as type I interferons induce a pleiotropic array of responses, including direct inhibition of growth of various tumors cells and modulation of host immune cells such as natural killer (NK) cells, 35,39,41,43,44,46 polymorphonuclear (PMN) cells, 43 macrophages, 36,39,41,47 CD4( þ ) 41,43 and CD8( þ ) 36,[41][42][43] cells. In most studies, as we observed in the experiments reported herein, local adenovirus mediated IFNb gene therapy was preferred over systemic due to increased local transgene concentrations and reduced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…36,37,40,41,47 On the other hand, systemic delivery of Ad-IFNb resulted in efficient hepatocyte transduction with the vector and potent liver metastases inhibition. 35,46 An interesting distinction between the two type I IFNs is the relative essential role for the effect of IFNb on stimulation of immune cells as there was a loss of efficacy in tumor bearing SCID-BEIGE. 42 In contrast, we observed significant efficacy with tumor IFNa treatment in immunocomprimised mice, suggesting the induction of responses not dependent on T-lymphocyte function, were sufficient to elicit tumor growth inhibition.…”
Section: Discussionmentioning
confidence: 99%